On Periodic Solutions of Degenerate Singularly Perturbed Linear Systems with Multiple Elementary Divisor - Akymenko, A. M.; Yakovets, V. P. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We establish sufficient conditions for the existence and uniqueness of a periodic solution of a system of linear differential equations with a small parameter and a degenerate matrix of coefficients of derivatives in the case of a multiple spectrum of a boundary matrix pencil. We construct asymptotics of this solution.